Мовний образ Криму в поезії Лесі Українки - Данилюк, Н. (Культура слова, 2020)
Статтю присвячен о мовному образу Криму, змодельованому на
основі поетичних текстів Лесі Українки із циклів «Кримські спогади»
(збірка «На крилах пісень», 1893), «Кримські відгуки», (збірка «Думи і
мрії», 1899) і двох поезій поза збірками. З’ясовано, що його формують
описи міст – Ялти, Євпаторії, Бахчисараю (особливо чітко постає
Бахчисарай як колишня ханська резиденція). За допомогою виразових
одиниць описано гори – Мердвен, Ай-Петрі та певні місця, пов’язані
з кримськими легендами (Байдари, Чортові сходи), передана стихія
Чорного моря. Лесин Крим асоціюється з близькими людьми –
братом та коханим, із кримськими татарами (найяскравіше
зображено дівчину-татарочку). Більшість загальних назв
півострова (край богоданний, ясна країна, сторона прекрасна та ін.)
мають позитивну конотацію. Окремі негативно-оцінні висловлювання
спричинені осмисленням занепаду традиційної кримськотатарської
культури, поневоленням корінного народу. The article is devoted to the linguistic image of the Crimea,
conceptualized on the basis of the analysis of Lesia Ukrainka’s poetic
texts from the cycles “The Crimean Recollections” (the collection “On
the Wings of Songs”, Lviv, 1893), “The Crimean Reminiscences” (the
collection “Thoughts and Dreams”, Lviv, 1899) and two poems “A Memory
from Yevpatoria” (1904) and “A Wave” (1908) which do not belong to any
collections. In these texts Lesya Ukrainka’s recollections about the visit
to the Crimea in 1890–1891, 1897–1898, and in 1907–1908 are reflected
with the help of figurative means. A linguistic image of the Crimea is a
segment of the individual-autho rial map of the world of the writer that
reflects her language-thinking, Ukrainian origin, and profound knowledge
of folklore resources. It has been found out that the image is consists of the
descriptions of such cities as Yalta, Yevpatoria, and Bakhchysarai where the
writer stayed or visited them. A special distinction is given to Bakhchysarai
with its realia of the khan’s palace and muslimness to which three poems
were devoted. With the help of figurative means the lines of mountains and
certain places, connected with the Crimean legends (Baidary, Chortovi
skhody (Devil’s stairs)), obtain their prominence. The nature and elements
of the Black sea are thoroughly depicted – quiet in the bright weather and
wild during the storm. Many contexts prove that the poetess perceived the
sea as a living creature, relevant to her moods and feelings. It has been
pointed out that Lesia’s Crimea is associated with her dear ones – first of
all with her brother Mykhailo and beloved Serhii, with the forgotten poet
Nadson, with the Crimean Tatars (the appearance and clothes of a young
female Tatar (who is called by a diminutive form of the ethnic name Tatar -
tatarochka) is described in the brightest way).
Most of the appellatives of the peninsular (God’s given land, a land
of constant rays, a bright country, a country of light, a joyful country,
a beautiful side (of the world) and others) have a positive connotation
caused by the author’s admiration of its gorgeous nature. But there
have been found negative evaluative expressions that resulted from the
understanding of the decay of the traditional Crimean Tatar material
and spiritual culture, enslavement of the indigenous people (Неволя
й досі править в сій країні! - Captivity still rules in this country!).
That is why the author compared the captivated land with a boat, broken
by a storm, and a steppe horse that dies in the sands of a desert.